Molecular basis of the NO trans influence in quaternary T-state human hemoglobin: A computational study - Petruk, Ariel Alcides (2013)
NO binding to the T-state of human hemoglobin (HbA) induces the cleavage of the proximal His bonds to the heme iron in the α-chains, whereas it leaves the β-hemes hexacoordinated. The structure of the nitrosylated T-state of the W37Eβ mutant (W37E) shows that the Fe-His87α bond remains intact. Exactly how mutation affects NO binding and why tension is apparent only in HbA α-heme remains to be elucidated. By means of density functional theory electronic structure calculations and classical molecular dynamics simulations we provide an explanation for the poorly understood NO binding properties of HbA and its W37E mutant. The data suggest an interplay between electronic effects, tertiary structure and hydration site modifications in determining the tension in the NO-ligated T-state HbA α-chain.